2001
DOI: 10.1097/00001756-200105250-00038
|View full text |Cite
|
Sign up to set email alerts
|

Phase-specific modulation of cortical motor output during movement observation

Abstract: The effects of different phases of an observed movement on the modulation of cortical motor output were studied by means of transcranial magnetic stimulation (TMS). A video-clip of a reaching-grasping action was shown and single TMS pulses were delivered during its passive observation. Times of cortical stimulation were related to the phases of the shown movement, locking them to the appearance of specific kinematic landmarks. The amplitude of the motor evoked potentials (MEPs) induced by TMS in the first dors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
254
4
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 383 publications
(289 citation statements)
references
References 17 publications
27
254
4
4
Order By: Relevance
“…The aim of this study was to disentangle the relative contribution and combination of different 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 14 person being observed and the observer's ones (Avenanti, Bolognini, Maravita, & Aglioti, 2007;Borroni et al, 2005;Borroni & Baldissera, 2008;Fadiga et al, 1995;Gangitano et al, 2001;Montagna et al, 2005;Strafella & Paus, 2000;Urgesi et al, 2006) and an anticipatory modulation of motor activations according to the final end of the perceived movement. While the video in which the soccer player suddenly stopped after kicking the ball ('still' condition) determined a decrease in CS excitability -signaling a transition to the motor profile designated by the action seen, observing the videos in which the player continued to run extended CS activity until the final phase of the action sequence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of this study was to disentangle the relative contribution and combination of different 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 14 person being observed and the observer's ones (Avenanti, Bolognini, Maravita, & Aglioti, 2007;Borroni et al, 2005;Borroni & Baldissera, 2008;Fadiga et al, 1995;Gangitano et al, 2001;Montagna et al, 2005;Strafella & Paus, 2000;Urgesi et al, 2006) and an anticipatory modulation of motor activations according to the final end of the perceived movement. While the video in which the soccer player suddenly stopped after kicking the ball ('still' condition) determined a decrease in CS excitability -signaling a transition to the motor profile designated by the action seen, observing the videos in which the player continued to run extended CS activity until the final phase of the action sequence.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of neurophysiologic studies have, moreover, demonstrated that action observation selectively activates the effector muscles involved in performing that action (for review see Fadiga, Craighero, & Olivier, 2005). The motor potentials (MEPs) evoked by transcranial magnetic stimulation (TMS) during action observation appear, in fact, to be specifically attuned to the muscles involved in the action being observed (Fadiga, Fogassi, Pavesi, & Rizzolatti, 1995;Sartori, Bucchioni, & Castiello, 2012a;Strafella & Paus, 2000;Urgesi, Candidi, Fabbro, Romani, & Aglioti, 2006) and to its temporal pattern (Aglioti, Cesari, Romani, & Urgesi, 2008;Borroni & Baldissera, 2008;Janssen, Steenbergen, & Carson, 2013;Kilner, Vargas, Duval, Blakemore, & Sirigu, 2004;Gangitano, Mottaghy, & Pascual-Leone, 2001;Urgesi, Maieron, Avenanti, Tidoni, Fabbro, & Aglioti, 2010). Behavioral studies have also demonstrated motor compatibility 4 effects, showing how the observation of a finger movement that corresponds to the instructed finger movement can facilitate the response (Brass & Heyes, 2005;Liepelt, Prinz, & Brass, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…both these assumptions are hard to reconcile with what is known about the organization of the cerebral cortex. Most importantly, TMS studies have shown a clear congruence between the observed motor act and the activated motor representation [32][33][34][35][36] . Thus, if higher-order sensory information describing a motor act reaches motor neurons that encode that same motor act, these motor neurons are mirror neurons by definition.…”
Section: Movementmentioning
confidence: 99%
“…The initial evidence for this mechanism was based on TMS experiments which indicated that the observation of the movements of others results in an activation of the muscles involved in the execution of those movements [32][33][34][35][36] . Additional support comes from eeG and MeG studies showing that the observation of movements without a goal desynchronizes the rhythms recorded from motor areas [57][58][59][60][61][62][63][64] .…”
Section: Box 1 | Mirror Neurons In Other Parietal Areasmentioning
confidence: 99%